ANALYSIS OF THE EFFECTIVENESS OF RURAL AND URBAN LAND AND BUILDING TAX (PBB P2) REVENUE AND ITS CONTRIBUTION TO LOCAL REVENUE IN BEKASI CITY IN 2016-2018 - Faisal H Batubara; Immi Fiska Tarigan; Tommy Kuncara (International Journal Multidisciplinary Science, 2023)
The objectives of this study are (1) to determine the level of effectiveness of Rural and Urban Land and Building Tax (PBB P2) in Bekasi City, and (2) to determine the level of contribution of Rural and Urban Land and Building Tax (PBB P2) to Regional Original Revenue (PAD) of Bekasi City. This research is quantitative descriptive research, which is based on the explanation of numbers. The data in this study are in the form of targets and realization of revenue from Rural and Urban Land and Building Tax (PBB P2) and the realization of Regional Original Revenue (PAD) of Bekasi City in 2016-2018. The results showed that the level of effectiveness of PBB P2 in 2016 and 2017 was in the effective category with a percentage of 99.64% and 96.19% respectively, while in 2018 it was in the highly effective category with a percentage of 122.59%. For the level of contribution of PBB P2 to Local Original Revenue (PAD), it shows that in 2016, 2017, and 2018 it was in the less category with a percentage of 15.52%, 15.06%, and 16.72% respectively.